Pendapat Bagi Hasil Tabungan IB Muaamalat Prim Terhadap Tingkat Kepuasan Nasabah - Wardatus Syarifah; Halimatus Saadah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Sharia banking is basically a development of the concept of Islamic economics, especially in the financial sector, which was developed as a response from economic groups and Muslim banking practitioners in the form of accommodating pressure from various parties who want financial transaction services carried out in line with moral values ​​and principles. Islamic sharia. Based on the Basic Banking Law Number 7 of 1992, which was reaffirmed by the issuance of Republic of Indonesia Law Number 10 of 1998, the type of sharia banking is Bank Muamalat Indonesia (BMI). Based on Law no. 10 of 1998 concerning banking, what is meant by savings are deposits from which withdrawals can only be made according to certain agreed conditions. The profits obtained by savers with this scheme are in the form of prizes, the amount of which is in accordance with the policies of each Sharia Bank. Savers who want a higher investment can choose the iB Muamalat Prima savings type with a profit sharing scheme. The research focus includes: 1) What is the influence of IB Muamalat Prima savings on the level of customer satisfaction at BMI KCP Sumenep? 2) What influence does IB Muamalat Prima's savings have on the level of customer satisfaction at BMI KCP Sumenep? In this writing, research is used. This research uses a quantitative approach, where research with a quantitative approach is defined as research where the data is in the form of numbers, taken from the population or samples, data collection using research instruments and analysis using statistical techniques, and aims to test the hypotheses that have been determined. Meanwhile, the type of research used is causality research. This research uses a quantitative approach, namely using statistical data analysis, while its nature is causality, namely cause and effect between two variables using statistical techniques. This research comes to the conclusion 1) Partially, profit sharing income has a significant influence on the level of satisfaction of BMI Kcp customers. Sumenep, this is indicated by the significance value of the profit sharing income variable of 0.000 which is smaller than the α value (0.05). 2) profit sharing income has an influence on the level of satisfaction of BMI Kcp customers. Sumenep was 29.9%, while 70.1% was influenced by other variables outside this research.